Imperialism in the Twentieth Century - Thornton, A. P. (Book collections on Project MUSE., 1978)
Nothing is filed under the heading?imperialism? in the archives of any nation-state that owned an empire. Foreign affairs, or external relations, are catalogued there, and a place is found for imperial administration and colonial trade; but?imperialism.